Design and performance of underground excavations Conception et comportement des excavations souterrains = Entwurf und Tragverhalten von Untertagehohlraumen : ISRM Symposium - Cambridge U.K., 3-6 September, 1984 - Brown, E. T. 1938-; Hudson, J. A. 1940- (British Geotechnical Society, 1984)
With contributions from twenty countries, this volume is a rich source of theory and experience in underground excavations for the researcher and practical engineering alike.